Metrologia: sua importância nas relações de consumo em face ao Sistema Nacional de Defesa do Consumidor - Feuz, Paulo Sergio (2010)
Upon the enactment of the 1988 Federal Constitution, a new stage takes place in Brazil: the democratic rule-of-law state. The grounds of this new politics formula are sovereignty citizenship, the dignity of the human person, and the social values of labor and of free enterprise system, as we]1 as political pluralism. In this context, it defined the protection of the consumers, settled in 1990 with the enactment of Law 8,078/90. The main concern of such legislation, which is presented in its National Policy for Consumption Relations, is to serve the consumers, by respecting their dignity, security and health, by protecting their economic interests and aiming at improving their life quality, thus implementing a National System for Consumer Defense. For this reason, and taking into account the concept of system for Law, the identification of subsystems which are able to meet the grounds of the democratic rule-of-law state, as well as the interests of the National Policy for Consumption Relations are indispensable. To that end, we take metrology as the central point, by analyzing all of the Law subsystem which are linked to it, and finally we discuss the complexity and the regeneration of Law as a whole